ANALISIS PENDAPATAN NELAYAN PADA KAPAL MOTOR 5-10 GT DI KABUPATEN ACEH BARAT DAYA - Zuriat Zuriat (Universitas Teuku Umar, 2016)
The potential of Marine Fishery in Aceh Barat Daya is a source of income for fishermen in meeting their household needs. The fact shows the great potential fishing has not been able to increase the income and welfare of the fishermen. This study aims at understanding the life of fishermen in terms of income and welfare. The method used in this research is descriptive method of sampling techniques by simple rand om sampling of the population 178 motor boats. The results showed that the income of the fishermen has been already above the poverty line although it is still under the World Bank’s standard. Of the expenditure, the primary need (food) is still greater so that it is concluded that the fishermen’s life is not yet welfare. It also demonstrated the value of the average income sea is below 1, and at 43,75 % NTN fisherman families under 1. For that reason, there is a need to develop the concept of the poverty line due to changes in the cost of primary needs such as children’s are concerned(snack), phone credits (communication) and motorcycle fuel (transportation). as well as the need to increase the number and size of motor boats in exploiting the potential of fish optimally while increasing the production of fishery products , which in turn increases the income and welfare of fishermen families .